PENGARUH JENIS SAMPAH PLASTIK TERHADAP HASIL BAHAN BAKAR MINYAK PADA REAKTOR PIROLISIS - Kemas Ridhuan; Riki Renaldi; Diego Armando (Universitas Muhammadiyah Metro, 2026)
Plastic waste has the disadvantage that it is difficult to decompose, so efforts are made to utilize it by converting it into fuel. One method that can be done is using the pyrolysis method, which is a decomposition process with little or no air. The purpose of this study was to determine the effect of the type of plastic waste on fuel oil yield and to determine the effect of time and temperature on the type of plastic in the pyrolysis process on a side stove. The research method used was experimental using types of plastic waste raw materials, namely Polyethylene Terephthalate (PET), Low Density Polyethylene (LDPE), and Polypropylene (PP). Using LPG as fuel. Using a condenser with two horizontal straight pipes. The results of this study indicate that variations in waste types affect fuel oil yield, temperature and combustion time. The highest temperature in the reactor occurred in the PP plastic variation with a temperature reaching 191°C with a combustion time of 195 minutes, and the lowest temperature in the reactor occurred in the LDPE and PET plastic variations with the highest temperature only reaching 184°C with a combustion time of 189 minutes for LDPE and 191 minutes for PET plastic. The highest amount of plastic oil was obtained from PET plastic waste, namely 331 grams, and the lowest amount was obtained from LDPE plastic waste, namely 305 grams.